The Development of Teaching Materials Gamification-Based Problem Solving on the Material in Terms of Four - Rizki Wahyu Yunian Putra; Jamal Fakhri; Dewi Fitriani (SAINTIS Publishing, 2019)
This study aims to develop teaching materials gamification-based problem solving on the material in terms of four. To view the judging of the validator against the feasibility of teaching materials gamification-based problem solving on the material terms of four and see the response of students to the attractiveness of the teaching materials gamification-based problem solving on the material in terms of four. This research use type research of research and development with a research model ADDIE (Analysis, Design, Development, Implementation and Evaluation. Stage of development (development) involving 9 validator (three validator matter experts, three media experts and three language experts) to assess the feasibility of the material, the media and the Indonesian language good and right. Stage of Implementation (field trials) involving 80 students ( 20 students trial of small group and 60 students test a large group). The assessment of the attractiveness of the teaching materials gamification-based problem solving on the material in terms of four using the questionnaire i.e. a questionnaire the validator and questionnaires of learners. Data analysis using descriptive analysis using Microsoft Office Excel 2010. The results of the validation matter experts from the 3 validator shows that the overall product to obtain an average value of 3.7 and the Results of the validation media experts obtained an average value of 3.3 while the results of the validation of language experts to obtain an average value of 3.4. While the results of the trials of a small group of 10 students of MTs N 1 Bandar Lampung obtained the results of the attractiveness of the teaching materials with an average value of 3.4. while the test is a large group that was conducted in SMP 30 Bandar Lampung to obtain an average value of 3.5. Thus, it can be concluded that the development of teaching materials gamification-based problem solving on the criteria of very worthy and interesting.